KONSEP NYUPAK DALAM KARAWITAN JAWA THE CONCEPT OF ‘NYUPAK’ IN JAVANESE TRADITIONAL MUSIC INSTRUMEN - Sito Mardowo (BBPPMPV Seni dan Budaya Yogyakarta, 2021)
The word ‘nyupak’ is a Javanese term which is often used in daily events or activities. ‘Nyupak’ is simply an activity of joining two objects so that the main object joined with another object can be used again according to its function. As a matter of fact, the term ‘nyupak’ is also used in karawitan organology in the process of (1) the tuning of ‘gender bumbungan’ (‘gender’ resonance) and (2) the tuning of gamelan, both in the form of blades and in the form of ‘pencon’. The current study aims at exploring the concept of ‘nyupak’ in Javanese traditional music instrument from acoustic perspective. The results of the study demonstrate that ‘nyupak’ in the tuning on ‘gender bumbungan’ (‘gender’ resonance) ranges from the intervals of 2 cents up to 12 cents, or written as 2 ≤ x ≤ 12 cents, and ‘nyupak’ in the tuning on gamelan ranges from the intervals of 10 cents up to 33 cents, or written as 10 ≤ x ≤33 cents. The result of the study provides a referential formulation for the tuning process of ‘gender bumbungan’ and gamelan, particularly to cope with ear sensitivity in capturing the tone frequency.